Natural History of Tricuspid Regurgitation After Transcatheter Aortic Valve Implantation - James A. Brown; Jack Donohue; Sarah Yousef; Nidhi Iyanna; Danial Ahmad; Dustin Kliner; Catalin Toma; Derek Serna‐Gallegos; Amber Makani; David West; Irsa Hasan; Takuya Ogami; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background To determine the impact of tricuspid regurgitation (TR) on outcomes after transcatheter aortic valve implantation (TAVI), and to determine the evolution of TR severity after TAVI. Methods This was an observational study of TAVIs for aortic stenosis from November 2012 to December 2021. Patients were dichotomized according to the severity of pre‐TAVI TR: less than moderate versus moderate or greater. Logistic regression was used to determine the risk factors for progression or persistence of moderate or greater TR at 1 year after TAVI. Results A total of 2250 patients were included for analysis, of which 301 (13.4%) had moderate or greater TR before TAVI. Baseline moderate or greater TR was associated with reduced survival and a higher incidence of heart failure readmission at 5 years after TAVI. Twelve percent of patients had progression or persistence of moderate or greater TR at 1 year after TAVI. On multivariable logistic regression, increasing age, female sex, lower mean pre‐TAVI aortic transvalvular pressure gradient, pulmonary artery systolic pressure ≥40 mm Hg, pulmonary vascular disease, and transfemoral vascular access were associated with progression or persistence of moderate or greater TR at 1 year after TAVI, while periprocedural variables related to valve implantation were not. Conclusions Significant TR before TAVI was associated with poor outcomes after TAVI. The incidence of moderate or greater TR at 1 year after TAVI was reasonable at 12%. Periprocedural factors, such as valve size, type of implanted valve, and paravalvular leak, were not associated with the development of TR. Evolution of TR and heart failure symptoms must be carefully surveilled after TAVI.